Homonationalist and homocolonialist discourses in Hong Kong's anti-extradition protests: Online evaluations and representations of LGBT rights. (April 2021) - Liu, Xuekun
Abstract: In this article I examine how some protesters perceived LGBT rights during the 2019–2020 Hong Kong protest movement. Discourse analysis is deployed to scrutinize one discussion thread on the online forum LIHKG, a thread mainly addressing the topic of an event announced as "protesting with you on Hong Kong tongzhi parade". The analysis focuses on how participants in the discussion thread evaluate and represent the event, LGBT rights, and the dyads of supporters/opponents of the activity, pro-democracy/pro-establishment Hong Kong citizens, and Hong Kong/Mainland people. The findings illuminate that while most participants use the discourse of freedom and democracy to express their support for LGBT rights and contest hegemonic heteronormative and heterosexist values, they largely enact and reproduce homonationalist and homocolonialist discourses, which I argue, can potentially limit the LGBT rights movement in Hong Kong.